The Hellenica Oxyrhynchia and historiography : new research perspectives - Occhipinti, Egidia. (Mnemosyne, Supplements, 2016)
This book involves a new historiographical study of the Hellenica Oxyrhynchia that defines its relationship with fifth- and fourth-century historical works as well as its role as a source of Diodorus' Bibliotheke . The traditional and common approach taken by those who studied the HO is primarily historical: scholars have focused on particular, often isolated, topics such as the question of the authorship, the historical perspective of the HO against other Hellenica from the 4th century BC. This book is unconventional in that it offers a study of the HO and fifth- and fourth-century historical works supported by papyrological enquiries and literary strategies, such as intertextuality and narratology, which will undoubtedly contribute to the progress of research in ancient historiography.